Cannabis sativa L. alleviates loperamide-induced constipation by modulating the composition of gut microbiota in mice - Li, Rong; Li, Min; Li, Bei; Chen, Wei‐Hua; Liu, Zhi (Frontiers in Pharmacology, 2022)
MaZiRenWan (MZRW) is the most frequently used Traditional Chinese Medicine formula to treat chronic constipation, Cannabis sativa L. is regarded as a monarch drug in MZRW. However, the targets of Cannabis sativa L. that enhance colonic motility and improve constipation symptoms remain unknown. This study was designed to investigate the laxative effect and underlying mechanism of the water extract of Cannabis sativa L. (WECSL) using a loperamide-induced constipation mouse model. We found that WECSL treatment significantly improved intestinal motility and water-electrolyte metabolism, decreased inflammatory responses, prevented gut barrier damage, and relieved anxiety and depression in constipated mice. WECSL also structurally remodeled the composition of the gut microbiota and altered the abundance of bacteria related to inflammation, specifically Butyricicoccus and Parasutterella. Moreover, WECSL failed to relieve constipation symptoms following intestinal flora depletion, indicating that WECSL alleviates constipation symptoms depending on the gut microbiota. Our research provides a basis for WECSL to be further investigated in the treatment of constipation from the perspective of modern medicine.